Influence of heating time and microwave radiation power on the microstructure and phase composition of calcium-phosphorus compounds during formation. (December 2020) - Khalugarova, K N; Maraeva, E V; Zaikina, A V; Matveev, V A; Moshnikov, V A
Abstract: This work is devoted to experimental methods for producing calcium-phosphorus compounds, including calcium hydroxyapatite, using microwave radiation. Two types of synthesis were used: template method and chemical precipitation. During synthesis, the heating time and power were changed. The obtained samples were studied using scanning electron microscopy, X-ray diffraction analysis, and the BET (Brunauer-Emmett-Teller) sorption method.